2006
DOI: 10.1182/blood-2006-03-009860
|View full text |Cite
|
Sign up to set email alerts
|

High molecular response rate of polycythemia vera patients treated with pegylated interferon  -2a

Abstract: V617F JAK2 mutation is a reliable molecular marker of polycythemia vera (PV), potentially useful to monitor the effect of treatments in this disease. In a phase 2 study of pegylated (peg) IFN-␣-2a in PV, we performed prospective sequential quantitative evaluation of the percentage of mutated JAK2 allele (%V617F) by realtime polymerase chain reaction (PCR). The %V617F decreased in 24 (89%) of 27 treated patients, from a mean of 49% to a mean of 27% (mean decrease of 44%; P < .001), and no evidence for a plateau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(175 citation statements)
references
References 15 publications
(14 reference statements)
6
163
1
4
Order By: Relevance
“…It is worthwhile that clinical improvements described in PV patients treated with recombinant interferon-a therapy, which included reduction of phlebotomy rate, of splenomegaly and of thrombo-hemorrhagic events, 36 were accompanied in one study by progressive decrease of JAK2 V617F allele amount in granulocytes. 37 Accurate determination of JAK2 V617F allele burden using quantitative assay, rather than merely defining heterozygosity versus homozygosity, and the fact that analysis was done at diagnosis rather than at variable times thereafter has been critical for better assessment of the prognostic role of JAK2 V617F allele. This has overcome the biases associated with previous studies that involved qualitative assays and heterogeneous patient series, and that led to conflicting results on the clinical significance of JAK2 V617F mutation in PV.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile that clinical improvements described in PV patients treated with recombinant interferon-a therapy, which included reduction of phlebotomy rate, of splenomegaly and of thrombo-hemorrhagic events, 36 were accompanied in one study by progressive decrease of JAK2 V617F allele amount in granulocytes. 37 Accurate determination of JAK2 V617F allele burden using quantitative assay, rather than merely defining heterozygosity versus homozygosity, and the fact that analysis was done at diagnosis rather than at variable times thereafter has been critical for better assessment of the prognostic role of JAK2 V617F allele. This has overcome the biases associated with previous studies that involved qualitative assays and heterogeneous patient series, and that led to conflicting results on the clinical significance of JAK2 V617F mutation in PV.…”
Section: Discussionmentioning
confidence: 99%
“…Peg-IFN-a2a in 27 PV patients, Kiladjian et al 73 showed a decrease of JAK2 mutant expression in 24 cases (89%) and in 1 patient mutant JAK2 was no longer detectable after 12 months of therapy. More limited effects on JAK2 mutational status have been reported after Peg-IFN-a2b therapy in a small group of patients with PV and ET.…”
Section: Spotlightmentioning
confidence: 99%
“…[18][19][20][21] Using quantification of JAK2V617F mutated alleles in circulating granulocytes as a marker of minimal residual disease, our group could also show that IFN-a was able to markedly decrease the proportion of circulating mutated cells. 22,23 The megakaryocytic lineage seems particularly sensitive to IFN-a, with clear morphological and biochemical changes of megakaryocytes in IFN-treated patients. 24 Furthermore, IFN-a is able to directly repress megakaryopoiesis by inhibiting thrombopoietin-induced Mpl receptor signaling.…”
Section: Rationale For Ifn-a In the Treatment Of Myeloproliferative Nmentioning
confidence: 99%